COMPARATIVE ANALYSIS OF PEDAGOGICAL TECHNOLOGIES OF PROFESSIONAL TRAINING OF GRAPHIC DESIGNERS IN UNIVERSITIES OF LEADING COUNTRIES OF THE WORLD - Inna Bykhovets ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
The worldwide trend in education is to train a professional who is able to respond quickly to the rapid development of information technologies that extend the graphic designer from the master of illustration, visual systems, advertising, and exhibition design to such areas of graphic design as moving graphics, interaction design, design animation, interactive design. The study found that the peculiarity of such training is the collaboration of educational institutions with enterprises, firms and institutions to make sure that the educational programs offered for students training meet the needs of production, and students really acquire the necessary knowledge, skills and competencies that are modern requirements for competitive graphic design specialist.